Sneathiella aquimaris sp. nov., isolated from aquaculture seawater. Issue 6 (29th June 2020) - Li, Guizhen; Lai, Qiliang; Yan, Peisheng; Gu, Li; Shao, Zongze
Abstract : A novel marine bacterium, designated strain 216LB-ZA1-12 T, was isolated from a Penaeus vannamei aquaculture seawater sample. Phylogenetic analysis based on 16S rRNA gene sequences indicated that strain 216LB-ZA1-12 T belonged to the genus Sneathiella, with the highest sequence similarity to Sneathiella glossodoripedis MKT133 T (97.7 %), followed by Sneathiella limimaris GH1-24 T (97.0 %), Sneathiella chungangensis CAU 1294 T (96.6 %) and Sneathiella chinensis LMG 23452 T (96.1 %). The average nucleotide identity and the DNA–DNA hybridization estimate values between strain 216LB-ZA1-12 T and four close type strains were between 69.2–71.3% and 16.7–17.8 %, respectively. The bacterium was Gram-stain-negative, facultatively anaerobic, oxidase and catalase positive, oval- to rod-shaped, and motile. Growth was observed at pH 7–9, salinities of 1–15% and temperatures of 4–42 °C. The G+C content of the chromosomal DNA was 48.50 mol%. The major respiratory quinone was determined to be Q-10. The principal fatty acids were summed feature 8 (C18 : 1 ω 7c/ ω 6c ) and C16 : 0 . The major polar lipids were diphosphatidylglycerol, phosphatidylethanolamine, phosphatidylglycerol, phosphatidylcholine and aminophospholipid. The combined genotypic and phenotypic data show that strain 216LB-ZA1-12 T represents a novel species within the genus Sneathiella, for which the name Sneathiella aquimaris sp. nov. is proposed, with the type strain 216LB-ZA1-12 T (=MCCC 1A14570 T =KCTC 72144 T ).